Survey on modern tools and methods of formal models verification - Kolchin, A.V.; Letichevsky, A.A.; Potiyenko, S.V.; Peschanenko, V.S. (PROBLEMS IN PROGRAMMING, 2015)
A survey on methods for automatic verificatoin of formal models of software systems is presented. Verifiable properties, methods of reduction and modern verification tools are considered.